Jane Austen - Lauber, John, 1925- (New York : Maxwell Macmillan International, 1993)
Discusses Austen's six novels--"Sense and Sensibililty," "Pride and Prejudice," "Mansfield Park," "Emma," "Persuasion," and "Northanger Abbey"--plus her other works and the reason she has still remained popular.
Includes bibliographical references (p. 151-153) and index.
Young Adult.
Young Adult
Keywords: Austen, Jane, -- 1775-1817 -- Criticism and interpretation; Austen, Jane, -- 1775-1817 -- Criticism